Gypenoside ameliorates insulin resistance and hyperglycemia via the AMPK-mediated signaling pathways in the liver of type 2 diabetes mellitus mice - Mengxue Song; Dehong Tan; Bin Li; Yanqun Wang; Lin Shi (Food Science and Human Wellness)
Gynostemma pentaphyllum, also called “Southern Ginseng” in China, is a traditional Asian folk medicinal plant. Gypenosides (Gps) are the biologically active constituents of G. pentaphyllum, which have been reported with hypoglycemic activity. However, the underlying mechanisms are unclear. The effects of two Gps (Gp-I and Gp-II) on type 2 diabetic mellitus (T2DM) mice, induced by high-fat and high-sugar diet and streptozotocin, were evaluated to explore the mechanism of their hypoglycemic actions. Gps reduced fasting blood glucose and serum lipids, as well as significantly improved T2DM mice glucose tolerance and insulin resistance (IR). After Gps treatment, the severity of liver injury was reduced and liver glycogen content increased. In addition, Gps promoted the phosphorylation of adenosine monophosphate-activated protein kinase (AMPK), and downregulated the key proteins phosphoenolpyruvate carboxy kinase and glucose-6 phosphatase, in the AMPK signaling pathway. Thus, our study suggests that Gps mediate hepatic gluconeogenesis and improve IR via activating AMPK signaling pathway in T2DM mice.